Advances in truck scheduling at a cross dock facility - Golias, Mihalis; Saharidis, Georgios K.D.; Ivey, Stephanie; Haralambides, Hercules E. (My University, 2013)
In this paper the authors deal with the scheduling of inbound and outbound trucks to the available inbound and outbound doors at a cross dock facility. They assume that all trucks served at the facility need to meet several deadlines for deliveries and pick-ups and thus request a departure time window from the facility, penalizing the facility operator, on a unit of time basis, if that deadline is not met. To solve the resulting problem with reasonable computational effort, a memetic algorithm is developed and a number of computational examples show the efficiency of the proposed solution algorithm and the advantages of scheduling inbound and outbound trucks simultaneously, as opposed to sequentially. Copyright © 2013, IGI Global.
Keywords: Truck Scheduling; cross dock facility